Armed conflicts and national trends in reproductive, maternal, newborn and child health in sub-Saharan Africa: what can national health surveys tell us?. (24th June 2019) - Boerma, Ties; Tappis, Hannah; Saad-Haddad, Ghada; Das, Jai; Melesse, Dessalegn Y; DeJong, Jocelyn; Spiegel, Paul; Black, Robert; Victora, Cesar; Bhutta, Zulfiqar A; Barros, Aluisio J D
Abstract : Armed conflicts are widespread in sub-Saharan Africa and considered to be an important factor in slowing down national progress in reproductive, maternal, newborn and child health (RMNCH). The measurement of the impact of conflicts on national levels and trends in RMNCH is difficult. National surveys conducted before and sometimes during and after conflicts are a major source of information on the national and local effects of conflicts on RMNCH. We examined data from national surveys in 13 countries in sub-Saharan Africa with major conflicts during 1990–2016 to assess the levels and trends in RMNCH intervention coverage, nutritional status and mortality in children under 5 years in comparison with subregional trends. The surveys provide substantive evidence of a negative association between levels and trends in national indicators of RMNCH service coverage, child growth and under-5 mortality with armed conflict, with some notable exceptions. National surveys are an important source of data to assess the longer term national consequences of conflicts for RMNCH in most countries, despite limitations due to sampling and timing of the surveys.